Comprehensive Association Analysis of 21-Gene Recurrence Score and Obesity in Chinese Breast Cancer Patients - Tong, Yiwei; Gao, Weiqi; Wu, Jiayi; Zhu, Siji; Huang, Ou; He, Jianrong; Zhu, Li; Chen, Weiguo; Li, Yafen; Shen, Kunwei; Chen, Xiaosong (Frontiers in Oncology, 2021)
Purpose A center-specific 21-gene recurrence score (RS) assay has been validated in Luminal-like, HER2-, pN0-1 Chinese breast cancer patients with both predictive and prognostic value. The association between RS and host factors such as obesity remains unclear. The objectives of the current study are to comprehensively analyze the distribution, single gene expression, and prognostic value of RS among non-overweight, overweight and obese patients. Patients and methods Luminal-like patients between January 2009 and December 2018 were retrospectively reviewed. Association and subgroup analysis between BMI and RS were conducted. Single-gene expression in RS panel was compared according to BMI status. Disease-free survival (DFS) and overall survival (OS) were calculated according to risk category and BMI status. Results Among 1876 patients included, 124 (6.6%), 896 (47.8%) and 856 (45.6%) had RS < 11, RS 11-25, and RS ≥ 26, respectively. Risk category was significantly differently distributed by BMI status (P=0.033). Obese patients were more likely to have RS < 11 (OR 2.45, 95% CI 1.38-4.35, P=0.002) compared with non-overweight patients. The effect of BMI on RS significantly varied according to menstruation (P<0.05). Compared to non-overweight patients, obese ones presented significantly higher ER, PR, CEGP1, Ki67, CCNB1 and GSTM1 (all P<0.05) mRNA expression, and such difference was mainly observed in postmenopausal population. After a median follow-up of 39.40 months (range 1.67-119.53), RS could significantly predict DFS in whole population (P=0.001). RS was associated with DFS in non-overweight (P=0.046), but not in overweight (P=0.558) or obese (P=0.114) population. Conclusions RS was differently distributed among different BMI status, which interacted with menopausal status. Estrogen receptor and proliferation group genes were more expressed in obese patients, especially in postmenopausal population.